Clinical, Hemato-Biochemical, and Diagnostic Studies of Peste Des Petits Ruminants (PPR) in Yearling Goats of Basrah, Iraq - Ali Jarad, Mohanad H. Lafta, Kamal M. Al Saad (Revista Electronica de Veterinaria, 2022)
Peste Des Petits Ruminants was detected in yearling goats by Eliza serodiagnosis at Basrah province of Iraq. One hindered fifty four (154) animals of 10-12 months old and of both sexes was examined and 25-yearling goats were considered as controls.  Results indicated that diseased yearling goats show signs of anorexia and depression, Dehydration with a rough coat and sunken eyes,  Diarrhea that mixed either with mucous or blood, Erosive mouth (erosive stomatitis)with frothy salivation, Conjunctivitis with obvious congestion of eyes and serious ocular discharge, and Pneumonia with abnormal lung sound on auscultation. Moreover, diseased animals show a significant rise in body temperature, and increase heart and respiratory rate. Leukocytopenia with lower lymphocyte count is a significant feature of hematological changes in infected goats in addition to increasing PCV and ESR values. A difference in clotting factor indices was also indicated in disease animals than in controls. Histopathological changes of diseased goats revealed a massive inflammatory infiltration (mostly lymphocytes) in the lamina properia of the villi mass as well as sloughing of the epithelium in the superficial intestinal layers.